Critical discourse analysis: towards a new perspective of efl reading - Débora de Carvalho Figueiredo (Ilha do Desterro)
Many researchers and theoreticians in the area of reading argue that to comprehend a text we need both linguistic knowledge of the language in which the text is written, and conceptual knowledge of the topic which is being addressed in the text (Carrell, 1988; Eskey & Grabe, 1988, etc.). However, another kind of knowledge can also help us in the process of text comprehension: a critical awareness of how linguistic practices and social practices are mutually supportive. Texts bear traces of the discourses and ideologies of the institutions which produce them (e.g. the media), and are also an arena for relations of social power and control. Since EFL students are exposed to texts from a different culture, their process of text comprehension can be enhanced if they are introduced to a critical perspective of reading, one that sees texts as historically, socially and culturally situated, establishing for writers and readers specific subject positions.